The economic impacts of tax-transfer policy : regional and distributional effects - Golladay, Fredrick L.; Haveman, Robert H. (Institute for Research on Poverty monograph series., 1977)
The Economic Impacts of Tax-Transfer Policy: Regional and Distributional Effects deals with evaluating proposed income-transfer policies through tax modeling. The book analyzes the direct and indirect effects of two variants of a negative income tax plan. These are the standard negative income tax and the Family Assistance Plan. By studying the indirect effects of income-maintenance programs on industries, occupations, and different regions, the authors point to understanding the effectiveness of alternative income-maintenance programs. Proposed changes in national taxes and transfer policies.